Implementation Of Green Accounting, CSR And Environmental Performance In Improving Financial Performance Moderized By GCG (Case Study at PT. Masmindo Dwi Area) - Riska Herman; Abid Ramadhan; Indah Pratiwi (LP2M IAIN Palopo, 2025)
In the era of globalization and increasing awareness of environmental issues, the application of the concept of green accounting and corporate social responsibility (CSR) is increasingly becoming a major concern in the business world. Both play an important role in improving the environmental and social performance of companies. Green accounting is a system or accounting approach that includes environmental considerations in financial recording and reporting. The purpose of green accounting is to measure and report the economic impact of . Improved financial performance can be influenced by the company's CSR practices. However, the effect of implementing this strategy on financial performance can be moderated by good corporate governance (GCG) practices. It states that good GCG can create transparency and accountability, and can strengthen the relationship between environmental performance and the company's financial performance. The purpose of this study was to determine the application of green accounting, corporate social responsibility, and environmental performance to the financial services of the company. PT Masmindo Dwi Area. This study uses a quantitative approach by distributing questionnaires to 96 employees of PT Masmindo Dwi Area in Luwu as respondents, who were selected through purposive sampling techniques. Data analysis was carried out using data quality tests, classical assumption tests, moderated regression analysis (MRA), and hypothesis testing. The results of the study show that green accounting, corporate social responsibility and environmental performance have a significant impact on financial performance and are moderated by good corporate governance.